The Equivocal Relationship Between Territoriality and Scent Marking in Wild Saddleback Tamarins (Saguinus fuscicollis) - Lledo-Ferrer, Yvan (Springer US, 2011)
Researchers have often assumed that scent marking serves a territorial function in callitrichines, although some controversy exists. To fulfill such a function, scent marks should 1) prevent intrusions, 2) ensure access to feeding resources, 3) enable avoidance of intergroup encounters, or 4) play an important role in the aggressive encounters between groups. We studied 13 saddleback tamarins (Saguinus fuscicollis) belonging to 3 free-ranging groups, which formed mixed-species troops with moustached tamarins (S. mystax) in the Amazonian rain forest of Peru. None of the predictions were confirmed. The tamarins used a border-marking strategy, marking more on the periphery of their territory. However, feeding trees in overlap and encounter areas received more scent marking but were still visited by neighboring groups. Intergroup encounters occurred more often than expected, and scent-marking frequency was not higher during them than when no other group was present. It appears that instead of defending a territory in the classic sense, the tamarins are optimizing signal transmission by depositing their scents where the probability of detection by neighbors is higher. Saddleback tamarins may use shared areas of their home ranges to exchange information with neighboring groups, perhaps regarding reproductive opportunities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10764-011-9516-9) contains supplementary material, which is available to authorized users.